Pembinaan Kesehatan Mental ODGJ Melalui Program Konseling Kristen di Panti Gerasa Kerawang - Romika Romika; Martauli Dina Rahayu Sitanggang; Endrow Dona; Shekinah Glory Mawuntu; Djeta Mara; Noni Indrawati Waruwu (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This community service program aims to improve mental health for individuals with mental disorders (ODGJ) through a Christian counseling approach at Panti Gerasa Kerawang. The activities are carried out by providing individual and group counseling sessions that integrate the principles of love, forgiveness, and healing from Christian teachings. Additionally, training is provided for the panti staff to strengthen their skills in supporting ODGJ with empathy and in alignment with spiritual values. The expected outcomes are an improvement in the quality of life of the panti residents through activities such as: 1) Joint Worship, 2) Group Games and Coloring, 3) Implementation of Counseling Sessions, and 4) Teaching and Counseling Training for Panti Staff. The conclusion of this program is expected to enhance the mental resilience of the residents and help them overcome the psychological challenges they face. Panti staff are also involved in training to strengthen their ability to conduct faith-based counseling approaches. At the end of the program, it is hoped that the residents will experience significant improvements in mental health and be better prepared to lead a more fulfilling life.